Forwarding in energy-constrained wireless information centric networks - Marques, Daniel Filipe Rodrigues (2022)
The objective of this work is the development of efficient forwarding in Energyconstrained Wireless Information Centric Networks (ICN). To achieve this goal, we will consider the type of devices, their internal energy, the network context and many other elements to implement the new content resolution for mobile wireless ICNs. The design, implementation and validation of the proposed forwarding was performed using the ndnSIM simulator, along with real datasets of boat mobility through the channels of "Ria de Aveiro" and buses in the city of Porto. Each day, Aveiro becomes a more and more smart city, and there is a forecast of making vehicles with low resources (for instance small and limited batteries), such as electric bicycles and the boats sailing on the "Ria de Aveiro", fully electric. There are a large number of people enjoying this kind of atractions to get around the city of Aveiro to get to know its history and culture, and consequently using their mobile devices as the main mean of communication, so energy management, both in vehicles and devices, is a very important task. Our proposal plans to help this project with a solution, that acts on the communication level and with the perspective of taking this solution to a real testbed in the city of Aveiro, that takes advantage of the network and node characteristics to create strategies and mechanisms for an efficient forwarding which allows reducing the energy spent on sending unnecessary packets and the overuse of resources, saving the energy of the network elements and ensuring a better content delivery. The results show that forwarding in wireless ICNs with these energy constraints resulted in significant improvements in network content availability, in the overall energy saving of the nodes and in the increase of the lifetime of the network, making the implementation a good choice for this kind of scenarios with high mobility (mobile ICNs), which was our main goal.